2017
DOI: 10.1080/09168451.2017.1373589
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid compounds related to seed coat color of wheat

Abstract: In red wheat, reddish-brown pigments accumulate in testa of mature seeds. Half-cut wheat seeds were immersed in p-dimethylaminocinnamaldehyde (DMACA) reagent that stains flavanol structures blue. Testa of 10-40 days after flowering (DAF) in red wheat ("Norin 61" and "Satonosora") seeds were stained blue and the reagent color changed to blue with 10-25 DAF seeds. No blue staining was observed in white wheat ("Tamaizumi") seeds during maturation. "Norin 61" seed coats at 10 DAF contained dihydroquercetin, dihydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 21 publications
1
30
0
Order By: Relevance
“…In both species polymeric phlobaphenes -substances related to 3-deoxyantocyanidins are present that differ them from the other cereals. Another polymeric flavonoids -proanthocyandins (PAs) are found at different concentrations and molecular forms in testa of sorghum [28], wheat [29], barley [30] and as evident from our study in rye, but not found at any tissues in maize. In rice PAs are found in pericarp of wild species Oryza rufipogon and red-grained varieties of O. sativa [31].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…In both species polymeric phlobaphenes -substances related to 3-deoxyantocyanidins are present that differ them from the other cereals. Another polymeric flavonoids -proanthocyandins (PAs) are found at different concentrations and molecular forms in testa of sorghum [28], wheat [29], barley [30] and as evident from our study in rye, but not found at any tissues in maize. In rice PAs are found in pericarp of wild species Oryza rufipogon and red-grained varieties of O. sativa [31].…”
Section: Discussionsupporting
confidence: 56%
“…Tannins are present in pigmented testa layer, their formation is determined by complementary genes B1 and B2 [32]. It is shown that B2 corresponds to gene Tan1 coding a WD 40 protein [28] and B1 is a gene of putative bHLH transcription factor Sb02g006390 [33].The color of testa is usually brown (Tp-) but it may be purple (tptp) [34]. The gene S controls the spreading of pigments from the testa to the pericarp being localized in cell walls of both tissues [35].…”
Section: Discussionmentioning
confidence: 99%
“…Oligomers and polymers of proanthocyanidins and their precursors flavan-3-ol units are detected by chemical agents (solution of vanillin in hydrochloric acid). The red color of the grain in wheat is explained by the accumulation in the testa of closely related flavonoid compounds, which are converted into a red-brown insoluble pigment as the kernels mature [ 15 ]. It was established that the accumulation in the testa of proanthocyanidins and their precursors in barley and wheat control the orthologous MYB-type transcription factors Hvmyb10 and Tamyb10, respectively [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The HPLC conditions mainly include the use of reverse phased C18 column, a binary solvent gradient, and different detection systems such as Diode Array Detection (DAD), MS or NMR (Marston & Hostettmann, 2006). HPLC methods have been successfully applied in DMY identification and quantification in healthy food for anti-hangover and hepatoprotection (Zou, Zhou, & Sun, 2017), in the fruit-stalk extract of H. dulcis (Park, Kim, & Rehman, 2016), in Yeputaoteng (Jin, Ding, & Zhang, 2014) and in red wheat (Kohyama, Chono, & Nakagawa, 2017). HPLC was also used for analysis of DMY content extracted from A. grossedentata by different extraction methods (Li, Li, & Zhang, 2008).…”
Section: Chromatographic Methodsmentioning
confidence: 99%